2009
DOI: 10.1029/2008jd011495
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields, conductivity, and estimated currents from aircraft overflights of electrified clouds

Abstract: [1] Using rotating vane electric field mills and Gerdien capacitors, we measured the electric field profile and conductivity during 850 overflights of clouds and thunderstorms. The measurements were made with NASA ER-2 and Altus-II aircrafts. Peak electric fields, with lightning transients removed, ranged from À1.0 kV m À1 to 16. kV m À1, with a mean value of 0.9 kV m À1. The median peak field was 0.29 kV m À1 . Flash rates ranged from 0 to over 27 flashes min À1 with the mean flash rate of 1.2 flashes min À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(109 citation statements)
references
References 50 publications
5
104
0
Order By: Relevance
“…They found that in general, the conductivity of the air above thunderstorms was not appreciably different from its value at the same altitude at distances far from the cloud. These results are supported by the Gerdien condenser measurements of Stergis et al (1957b) and Blakeslee et al (1989) both from balloon platforms, and Bailey et al (1999) and Mach et al (2009), both from aircraft platforms. Measurements of conductivity above storms using the relaxation technique from a constant level balloon platform, however, have found contradictory results (e.g.…”
Section: Conductivity Above Thunderstormssupporting
confidence: 78%
See 1 more Smart Citation
“…They found that in general, the conductivity of the air above thunderstorms was not appreciably different from its value at the same altitude at distances far from the cloud. These results are supported by the Gerdien condenser measurements of Stergis et al (1957b) and Blakeslee et al (1989) both from balloon platforms, and Bailey et al (1999) and Mach et al (2009), both from aircraft platforms. Measurements of conductivity above storms using the relaxation technique from a constant level balloon platform, however, have found contradictory results (e.g.…”
Section: Conductivity Above Thunderstormssupporting
confidence: 78%
“…The exponential decay to background levels after this increase was observed to occur during a timescale of ≈50 seconds, consistent with the relaxation time in ambient air at those altitudes. Transients in electric field above thunderstorms due to lightning discharges have also been observed on a large number of flights by Mach et al (2009). Their study contains the most extensive set of measurements of electrical properties above thunderstorms, taken from 850 flights over electrified clouds during a ten year period.…”
Section: Above Storm Topsmentioning
confidence: 99%
“…The diurnal variation with local time for all the continents individually showed peak around 1600 h local time (Bailey et al, 2007). The land-based storms have a much larger mean flash rate (40 s À 1 ) and also larger variation between peak and trough than ocean lightning storms (mean 5 s À 1 ), which almost shows a constant value (Mach et al, 2009(Mach et al, , 2010.…”
Section: Convection Over Land and Ocean Surfaces And Lightningmentioning
confidence: 98%
“…Measurements of electric fields within clouds have been made using aircraft for many years (e.g., Winn 1993;Merceret et al 2008;Mach et al 2009). Retrieving electric field components from the raw aircraft field mill data while in cloud is perhaps the most difficult aspect of the measurement process because of the usually high charging of the aircraft (e.g., Jones 1990;Koshak et al 1994;Koshak 2006;Koshak et al 2006;Mach and Koshak 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving electric field components from the raw aircraft field mill data while in cloud is perhaps the most difficult aspect of the measurement process because of the usually high charging of the aircraft (e.g., Jones 1990;Koshak et al 1994;Koshak 2006;Koshak et al 2006;Mach and Koshak 2007). The electric field as measured by an instrument on the aircraft includes linear components from the external electric field e X , e Y , e Z , charge on the aircraft (e Q ), mill offset, and various other phenomenon, including measurement errors and nonlinear terms (l).…”
Section: Introductionmentioning
confidence: 99%